Comparative Analysis of Financial Inclusion in Developing Regions Around the World - Meldina Kokorovic Jukan; Amra Softic (Economic Review: Journal of Economics and Business, 2016)
Financial inclusion is perceived as an enabler of poverty reduction around the world and today is in agenda of all policy makers in both developed and developing countries. In order to emphasize the importance of financial inclusion and provide an insight to the level of financial inclusion around the world, this paper investigates the extent of financial inclusion in different developing regions around the world. The paper investigates developing regions (Eastern, South and Central Asia, Latin America, Sub-Saharan Africa, and the Western Balkans) because population of these regions is at the highest risk of financial exclusion. Using secondary data from existing the Global Findex data base, this paper shows low levels of financial inclusion in developing regions.
Keywords: G21; O16; 330; financial inclusion; developing regions